Developing microcontroller–based sorting and placing robots in automation practice subject of vocational high school - Sukir, -; Yatmono, Sigit (JOURNAL OF EDUCATION, 2015)
This study was aimed at developing microcontroller–based sorting and placing robots as training kit of Otomation Practice subject in Vocational High School. The study was research and development involving six steps: need assesment, planning, developing, testing, repairing, and ï¬ nishing. The subjects were10 teachers of Industrial Electronic Study Program of Vocational High School.Data were collected using an observation guide, and analyzed quantitatively usingdescreptive statistic in the form of means. Findings of the study showed that themicrocontroller–based sorting and placing robots had been developed with goodfeasibility degree, which was shown by expert validation average score of 2.93